Alkaline phosphatase localization in golden hamster epididymidis: A biochemical and histochemical investigation - Beu, C. C L; Orsi, A. M. [UNESP]; Novelli, E. L B [UNESP]; Domeniconi, R. F. [UNESP]; Burneiko, R. C. [UNESP]; Galhardi, C. M. [UNESP] (My University, 2007)
The aim of this study was to determine alkaline phosphatase (ALP; E.C. 3.1.3.1) activity and major expression in homogenates obtained from different regions of Golden hamster epididymis, comprising the initial segment, head, body and tail, with concomitant research of this enzyme localization and activity in samples of tissues. These were collected from the same regions and investigated by histochemical conventional study performed on frozen histological sections. No significant differences in mean ALP activity, reported as U.100 mg-1 of tissue, were observed among the biological specimens collected from the epididymidis initial segment (0.92 ± 0.28 U.100 mg-1 tissue), head (1.07 ± 0.67 U.100 mg-1 tissue) and body (0.77 ± 0.23 U.100 mg-1 tissue). However, mean ALP activity was significantly higher in the epididymal tail (8.94 ± 0.40 U.100 mg-1 tissue) compared with the precedent segments. The findings suggested that ALP plays a significant role in the tail of the Golden hamster epididymidis, mediating androgenic segregation necessary to maintain the epithelial integrity. Furthermore, ALP acts on active transport of substances between the luminal fluid and spermatozoon membrane, and contrariwise. Thus, the high concentration of ALP in the epididymal tail helps to indicate the importance of this enzyme in the metabolism and maintenance of spermatozoa maturation and storage into the epididymidis luminal compartment, perhaps directly influencing the normal reproductive morphophysiology.
Keywords: Alkaline phosphatase; Biochemistry; Epididymidis regions; Hamster; Histochemistry